2010
DOI: 10.1007/s00148-010-0328-6
|View full text |Cite
|
Sign up to set email alerts
|

Segregation, entrepreneurship and work values: the case of France

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 35 publications
2
8
0
Order By: Relevance
“…Belzil and Poinas (2010) confirm this educational gap between workers of North African and French origin and they conclude that this affects the hiring process and wages of the secondgeneration immigrants in the labour market. Second, differences of behaviour at work observed among the different minorities in France, as put forwards by Senik and Verdier (2011) justify differences on the labour market. Third, the importance of housing: the fact that African immigrants are mostly in social housing and in ZUS decreases their likelihood of access to employment as correspondence studies show.…”
Section: Resultsmentioning
confidence: 99%
“…Belzil and Poinas (2010) confirm this educational gap between workers of North African and French origin and they conclude that this affects the hiring process and wages of the secondgeneration immigrants in the labour market. Second, differences of behaviour at work observed among the different minorities in France, as put forwards by Senik and Verdier (2011) justify differences on the labour market. Third, the importance of housing: the fact that African immigrants are mostly in social housing and in ZUS decreases their likelihood of access to employment as correspondence studies show.…”
Section: Resultsmentioning
confidence: 99%
“…A French study finds that North African immigrants tend to have a lower attachment to work values than French natives. However, this difference disappears when the researchers control for the extent to which the participants' network includes entrepreneurs (Senik and Verdier, ). A contrasting result is put forward by Koopmans (), who found that stronger assimilation to host country values in terms of general gender equality decreases the risk of being unemployed, though the assumed direction of causality can be disputed.…”
Section: Literature and Hypothesesmentioning
confidence: 99%
“…(2002), Francois and Zabojnik (2005) and Estrella López (2003) for social capital; Saez- Marti and Zenou (2005) and Senik and Verdier (2007) for work values and ethnic labor market discrimination; Francois (2006) and Bidner and Francois (2009),for the evolution of informal institutions; Frot (2008) for cultural transmission through friendship formation; Hiller (2008a) for preferences for autonomy and work organization; Hiller (2008b) for pro-social preferences and corporate culture; Baudin (2008) for fertility; Ponthiere (2008) for lifestyles transmission and longevity; Melindi Ghidi (2009) for political ideology; Correani, Di Dio, and Garofalo (2009) for tolerance; Frot (2009) and Michaud (2008) for work values and social/unemployment insurance. We cannot discuss them in any detail, for obvious space limitations.…”
Section: Cultural Transmission and Social Interactionsmentioning
confidence: 99%